ENGLISH WRITING MATERIALS BASED ON LOCAL NEEDS FOR STUDENTS IN REMOTE AREAS - Aspiandi, .; Sutapa. Y, Y. Gatot; ., Sudarsono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The objective of the study is to develop supplementary writing materials based on local needs for remote area students at SMPN 3 Satap Toba. This research is Research and Development method with the adaptation of the development proposed by David Jolly and Rod Bolithoâ€™s framework. To get the data of local needs, thus identification of needs is done. The data derived from the questionnaires, interview, and direct observation. The evaluation showed that besides the good points, there were still a number of weak points. The weak ones were revised according to the feedbacks and suggestions from the experts. The feedbacks from the students suggested adding some photographs and clear instructions. After some revisions from the feedbacks and suggestions from the expert, the final product was completed. Because teachers know their studentsâ€™ needs, thus English language teachers are recommended to write their own supplementary material based on local needs. Â Keywords: Local Needs, Writing, Material, Remote area Abstrak: Penelitian ini bertujuan untuk mengembangkan materi suplement menulis berdasarkan kebutuhan lokal untuk pelajar yang ada di daerah terpencil khususnya SMPN 3 Satap Toba. Penelitian ini dilakukan dengan metode Research and Development dengan mengadaptasi model pengembangan dari David Jolly dan Rod Bolitho. Untuk mendapatkan data tentang kebutuhan lokal, maka analisis kebutuhan diperlukan. Data diperoleh dari kuisioner, wawancara dan observasi langsung. Dari hasil evaluasi menunjukkan bahwa disamping ada hal baik, ada juga beberapa kekurangan. Kekurangannya diperbaiki berdasarkan umpan balik dan saran dari para ahli. Umpan balik dari siswa-siswi adalah menambahkan beberapa photo asli and kejelasan perintah pada material. Setelah perbaikan dan saran dari para ahli, jadilah produk akhir. Karena guru lah yang mengetahui kebutuhan peserta didiknya maka guru bahasa Inggris di rekomendasikan untuk menulis materi suplement yang digunakan di kelasnya berdasarkan kebutuhan lokal. Kata kunci: Kebutuhan Lokal, Menulis, Material, Daerah terpencil